If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 3 = -5(x + 7) + 8 Reorder the terms: 3 + 10x = -5(x + 7) + 8 Reorder the terms: 3 + 10x = -5(7 + x) + 8 3 + 10x = (7 * -5 + x * -5) + 8 3 + 10x = (-35 + -5x) + 8 Reorder the terms: 3 + 10x = -35 + 8 + -5x Combine like terms: -35 + 8 = -27 3 + 10x = -27 + -5x Solving 3 + 10x = -27 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 3 + 10x + 5x = -27 + -5x + 5x Combine like terms: 10x + 5x = 15x 3 + 15x = -27 + -5x + 5x Combine like terms: -5x + 5x = 0 3 + 15x = -27 + 0 3 + 15x = -27 Add '-3' to each side of the equation. 3 + -3 + 15x = -27 + -3 Combine like terms: 3 + -3 = 0 0 + 15x = -27 + -3 15x = -27 + -3 Combine like terms: -27 + -3 = -30 15x = -30 Divide each side by '15'. x = -2 Simplifying x = -2
| x-2/5=61/4 | | (2x-6)(10x^2-24x+9)=0 | | (2/14)+(1/2p)=(1/7) | | 1/2m+12=48 | | (3x+7)/(5)-2=9 | | x-2(3x+24)=3x | | 2/3(4x+2)=3(1-2x)+7 | | -8-5z=0+9z | | 11/14x=22 | | X-7+3(2x+1)=-7(x+2) | | -5x+9=-49 | | -4x+7(x+3)=8x+14 | | -23-4x=13+10x | | -58+22=-6x+15x | | 8n+12-5n=12 | | (5)/(x+6)=-(3)/(2x+12)+1 | | 9x*16x=3300 | | x-7=x+23 | | 5x/(x+4)+3x/(x-5) | | 13x-17=3x-(56/8) | | 6/2x+3=30 | | -w/0.2=15.4 | | 9(X-3)=-3(2X+14) | | 13x-17=3x-7 | | (3/10)=(5x+1)/(18x-6) | | 10.36=2.7y | | (3/10)=(5x+1)/(18-6) | | x^2-4x-84=0 | | 7+3x=4x | | 2(a+3)+3(2a-1)= | | 4/2x+10=2x | | x^3+7x^2-8x+90=0 |